ENT600: Klinik Pergigian Dr. Aini / Fatin Shafikah Ribuan … [et al.] - Ribuan, Fatin Shafikah; Mohd Nor Azmi, Nur Afiqah; Abu Bakar, Nor Aziyati; Mohd Salleh, Nurul Syuhada; Saad, Siti Hajar (2018)
This paper is focus on a case study of a company called Klinik Pergigian Dr. Aini. It has been establishes in year 2017 on 7th September and was located at Tanjong Karang, Selangor. For this purpose, we have an interview session with the owner about the company information and did SWOT analysis. The services provided by Dr. Aini includes diagnosis oral diseases, dental care and treatments and referral to medical care or dental specialists. The major problem faced by Klinik Pergigian Dr. Aini was a limited financial resources. Meanwhile, the financial problems is closely related to economic burden in Malaysia. The prices of dental supplies become more expensive due to new taxes introduced by government. However, Dr. Aini needs to face the problem.